Acacetin alleviates autoimmune myocarditis by regulating CD4+ T cell mitochondrial respiration - Yang Lu; Yu-Wei Wu; Jiu Pu; Qiong-Feng Wu; Qian Dong; Ning Zhao; Gui-Rong Li; Yi-Mei Du (BMC, 2024)
Abstract Background Myocarditis refers to an autoimmune inflammatory response of the myocardium with characterization of self-reactive CD4+ T cell activation, which lacks effective treatment and has a poor prognosis. Acacetin is a natural flavonoid product that has been reported to have anti-inflammatory effects. However, acacetin has not been investigated in myocarditis. Methods Oral acacetin treatment was administered in an experimental autoimmune myocarditis model established with myosin heavy chain-alpha peptide. Echocardiography, pathological staining, and RT-qPCR were used to detect cardiac function, myocardial injury, and inflammation levels. Flow cytometry was utilized to detect the effect of acacetin on CD4+ T cell function. RNA-seq, molecular docking, and microscale thermophoresis (MST) were employed to investigate potential mechanisms. Seahorse analysis, mitoSOX, JC-1, and mitotracker were utilized to detect the effect of acacetin on mitochondrial function. Results Acacetin attenuated cardiac injury and fibrosis as well as heart dysfunction, and reduced cardiac inflammatory cytokines and ratio of effector CD4+ T and Th17 cells. Acacetin inhibited CD4+ T cell activation, proliferation, and Th17 cell differentiation. Mechanistically, the effects of acacetin were related to reducing mitochondrial complex II activity thereby inhibiting mitochondrial respiration and mitochondrial reactive oxygen species in CD4+ T cells. Conclusion Acacetin may be a valuable therapeutic drug in treating CD4+ T cell-mediated myocarditis. Graphical Abstract